SPE Latin American and Caribbean Petroleum Engineering Conference 2003
DOI: 10.2118/81094-ms
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Solid Expandable Tubular Technology Reliability in a Myriad of Downhole Environments

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractSince the spectacular arrival of solid expandable tubulars four years ago, customers have embraced this technology as a revolutionary well construction and production solution. Through innovative technical development and equipment reliability, solid expandable tubulars continue to grow in acceptance and use.Solid expandable tubulars have been used successfully to reach required total depth (TD) with adequate completion size, slim the well construction proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This technology can also be used in different types of wells as in multiple fixing wells, high-angle and horizontal wells, and in deep and hot wells. Several field trials [2][3][4][5][6][7] proved the viability of this technology as a solution to aging wells. Other research work related to simulation of downhole solid tubular expansion field cases was performed by Pervez et al [8] and Seibi et al [9] to study the effect of the expansion ratio, cone angle, and friction coefficient on the expansion force and showed that the drawing force increases when the friction coefficient, mandrel angle, and expansion ratio increase.…”
Section: Introductionmentioning
confidence: 99%
“…This technology can also be used in different types of wells as in multiple fixing wells, high-angle and horizontal wells, and in deep and hot wells. Several field trials [2][3][4][5][6][7] proved the viability of this technology as a solution to aging wells. Other research work related to simulation of downhole solid tubular expansion field cases was performed by Pervez et al [8] and Seibi et al [9] to study the effect of the expansion ratio, cone angle, and friction coefficient on the expansion force and showed that the drawing force increases when the friction coefficient, mandrel angle, and expansion ratio increase.…”
Section: Introductionmentioning
confidence: 99%
“…To date, over 250 solid expandable tubular installations have been performed, and more than 250,000 ft of pipe expanded. 2 The combination of a steadily increasing success rate and a greater understanding of the benefits of the technology led a major international operator to use solid expandable casing in a well in Africa. The success in West Africa led to two additional installations of solid expandable tubulars in other regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this technology is used to increase the rate of production by enlarging the volume of the production tubing as well as sand control screens in open holes. Several studies related to SETT have been performed over the last two decades 2–5 and proved its viability in field applications 6–12 . However, very limited studies dealing with expansion of sand control screens have been conducted 11 …”
mentioning
confidence: 99%
“…Several studies related to SETT have been performed over the last two decades 2-5 and proved its viability in field applications. [6][7][8][9][10][11][12] However, very limited studies dealing with expansion of sand control screens have been conducted. 11 The challenge that remains facing field engineers in deep wells with corrosive environments is the selection of appropriate corrosion resistant alloys that can sustain large expansion ratios up to 25% without jeopardizing their strength especially in the presence of perforations at the base pipe of sand control screens.…”
mentioning
confidence: 99%